2018
DOI: 10.1002/gps.4997
|View full text |Cite
|
Sign up to set email alerts
|

Timely diagnosis of dementia? Family carers' experiences in 5 European countries

Abstract: Objectives Timely diagnosis of dementia is recommended in national strategies. To what extent is it occurring across Europe, what factors are associated with it, and what is the impact on carers emotions of quality of diagnostic disclosure? Methods/design Survey of family carers recruited through 5 Alzheimer's associations (Czech Republic, Finland, Italy, the Netherlands, and Scotland). One thousand four hundred and nine carers participated, 84% completing online. Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 8 publications
2
62
0
1
Order By: Relevance
“…Reducing uncertainty could facilitate the start of the acceptance process in cases of cognitive impairment. This is in line with a recent study that showed that an early diagnosis with high quality diagnostic disclosure was associated with better adjustment and less negative emotional impact both in the short and the long term (Woods et al, 2019). In our study, patients without a cognitive impairment were relieved when they learned that the NPA was going well.…”
Section: Discussionsupporting
confidence: 92%
“…Reducing uncertainty could facilitate the start of the acceptance process in cases of cognitive impairment. This is in line with a recent study that showed that an early diagnosis with high quality diagnostic disclosure was associated with better adjustment and less negative emotional impact both in the short and the long term (Woods et al, 2019). In our study, patients without a cognitive impairment were relieved when they learned that the NPA was going well.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the length of time between dementia symptoms being noticed and diagnosis of dementia has been estimated to vary in Europe from 1.61 years in Italy to 2.49 years in Scotland and 2.57 years in Netherlands. 46 Therefore, comparisons are limited with epidemiological cohorts using dementia screening protocols. At least some of the widening difference in exposure levels between cases and controls may, therefore, have occurred during times when dementia was evident but undiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The positive experiences reported by the majority of carers in this European sample appear to be an unusual finding in the literature, which largely reports barriers to service use. Furthermore, a recent study reported a lack of timely diagnosis of dementia and carers’ experiences of delays (Woods et al , 2018). The barriers reported in this study are in line with previous research reporting barriers to service use (Vetter et al ., 1998; Buono et al ., 1999; Brodaty et al ., 2005; Greenwood and Smith, 2015).…”
Section: Discussionmentioning
confidence: 99%